MEMBENTUK PEMIMPIN KRISTEN DALAM DUNIA PENDIDIKAN: HUBUNGAN BUDAYA, SPIRITUALITAS, DAN ILMU KETENAGA PENDIDIKAN - Yosindra Birrik; Glory Cristi Ayamisyeba, Sarah Cecilia Amunauw, Iriyani Maryar, Agustina Kapisa Budaya dan Kepemimpi (ADISAM PUBLISHER, 2025)
Christian leadership in education plays an important role in forming leaders who are not only academically competent, but also have strong character and are based on Christian values. This article examines the role of culture, spirituality, and educational science in forming effective Christian leaders in educational environments. Culture, with all its values and traditions, has a major influence on how a leader thinks and acts. Spirituality, as the main foundation of Christian leadership, guides leaders to lead with love, integrity, and wisdom. Meanwhile, educational science provides a technical and strategic basis for managing educational institutions. This article also discusses the challenges faced in implementing Christian leadership in modern education and the strategies that can be used to deal with them. By integrating these three aspects, Christian education can create leaders who are holistic, have character, and are ready to bring about positive change